2023
DOI: 10.1007/s11846-023-00621-4
|View full text |Cite
|
Sign up to set email alerts
|

Can artificial intelligence’s limitations drive innovative work behaviour?

Abstract: Artificial intelligence (AI) is deemed to increase workers' productivity by enhancing their creative abilities and acting as a general-purpose tool for innovation. While much is known about AI's ability to create value through innovation, less is known about how AI's limitations drive innovative work behaviour (IWB). With AI's limits in perspective, innovative work behaviour might serve as workarounds to compensate for AI limitations. Therefore, the guiding research question is: How will AI limitations, rather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 142 publications
0
3
0
Order By: Relevance
“…For instance, Oppi et al (2020) [8] stress that employees use IWB as a problem-focused strategy to cope with intensified task requirements when confronting career challenges. Zirar (2023) [9] suggests that when perceiving more threats or fewer opportunities for future career development, employees may participate in innovative vocational behaviors like job crafting. On the downside, other scholars argue that striving for career sustainability can sometimes hurt workers' well-being, potentially stifling their passion for innovation.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Oppi et al (2020) [8] stress that employees use IWB as a problem-focused strategy to cope with intensified task requirements when confronting career challenges. Zirar (2023) [9] suggests that when perceiving more threats or fewer opportunities for future career development, employees may participate in innovative vocational behaviors like job crafting. On the downside, other scholars argue that striving for career sustainability can sometimes hurt workers' well-being, potentially stifling their passion for innovation.…”
Section: Introductionmentioning
confidence: 99%
“…AI ethics awareness and attitude toward AI affect nursing behavior [ 13 ]. AI has been proposed to boost nurses’ creativity, which boosts productivity [ 14 ], as shown in a conceptual model Fig. 1 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 , 18 , 20 , 21 ]. Furthermore, Zirar (2023) demonstrated that by fostering creativity and serving as a versatile tool for innovation, artificial intelligence (AI) has the potential to enhance workers’ productivity [ 22 ]. Hence, for nurses to enhance their knowledge and deliver high-quality care, it is crucial for them to understand AI and ethical concepts and to have a positive attitude towards them.…”
Section: Introductionmentioning
confidence: 99%